2013
DOI: 10.2478/lpts-2013-0024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Pre-Processing of Pelletized Biomass on its Gasification and Combustion / Mikroviļnu Priekšapstrādes Ietekme Uz Granulētas Biomasas Gazifikācijas Un Degšanas Procesiem

Abstract: To effectively produce clean heat energy from biomass, microwave (mw) pre-processing of its different types - pelletized wood (spruce), herbaceous biomass (reed canary grass) and their mixture (50:50) - was carried out at the 2.45 GHz frequency with different durations of biomass exposure to high-frequency oscillations. To estimate the mw pre-processing effect on the structure, composition and fuel characteristics of biomass, its thermogravimetric (TG), infrared spectroscopy (FTIR) measurements and elemental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Previous studies confirm that these factors also significantly affect the thermochemical conversion of different origin lignocellulosic biomass pellets and their mixtures [7]. An increase of the mw pretreatment time correlates with an increase in weight loss of biomass samples, mainly due to the evaporation of physically bounded moisture, partial thermochemical degradation of biomass carbohydrates and the release of volatile compounds, which depends on the chemical composition of the raw biomass [7]. Thus, there are several factors determining the efficiency of biomass mw pretreatment; to achieve effective control of the combustion characteristics and composition of emissions, detailed studies must be conducted to determine the main effects responsible for the thermal decomposition of activated biomass pellets as well as the formation of combustible volatiles and their ignition, combustion, heat energy production and composition of emissions.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Previous studies confirm that these factors also significantly affect the thermochemical conversion of different origin lignocellulosic biomass pellets and their mixtures [7]. An increase of the mw pretreatment time correlates with an increase in weight loss of biomass samples, mainly due to the evaporation of physically bounded moisture, partial thermochemical degradation of biomass carbohydrates and the release of volatile compounds, which depends on the chemical composition of the raw biomass [7]. Thus, there are several factors determining the efficiency of biomass mw pretreatment; to achieve effective control of the combustion characteristics and composition of emissions, detailed studies must be conducted to determine the main effects responsible for the thermal decomposition of activated biomass pellets as well as the formation of combustible volatiles and their ignition, combustion, heat energy production and composition of emissions.…”
Section: Introductionmentioning
confidence: 79%
“…Previous experimental studies evaluating the effect of mw pretreatment on the thermal decomposition of biomass samples of different origins and parameters characterizing the combustion process have shown that microwave-induced oscillations produce variations in the biomass structure, composition, and the heating value. This results in a decrease of the mass density of pretreated biomass, faster thermal decomposition, faster yield, ignition, and burnout of combustible volatiles, an increase in the energy output and average values of carbon-neutral CO2 emissions in the products [7,8]. Furthermore, results of previous experimental studies have shown that the effect of mw pretreatment on combustion characteristics is highly influenced by the chemical composition of the lignocellulosic biomass content of hemicelluloses, cellulose and lignin, with a more pronounced effect of mw pretreatment on the combustion characteristics for straws with a higher content of hemicellulose in biomass [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While removal of moisture and drying residual biomass is widely accepted to be used for regional sustainable energy systems [13], the technology of MW pretreatment can be applied for a variety of biomass types [14][15][16] and has advantages over conventional thermal preprocessing. It can provide faster and more uniform spatial heating of biomass with a faster thermal destruction of hemicelluloses and cellulose and thermochemical conversion of pretreated biomass [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies suggest that additional measures are needed to improve the process development when co-combusting different origin pelletized fuels. With reference to the studies of the effect of MW pre-treatment on lignocellulosic biomass samples [9][10][11], it is suggested that an improvement of combustion characteristics when co-combusting different pelletized fuels can be achieved by selective microwave (2.45 GHz) pre-treatment of the mixture components. This leads to the activation of thermal decomposition of hemicellulose, cellulose and lignin of the pre-treated components.…”
Section: Introductionmentioning
confidence: 99%